Studi Literatur Surealisme di Indonesia - Mega Iranti Kusumawardhani; Muhammad Cahya Mulya Daulay (ULTIMART Jurnal Komunikasi Visual, 2021)
This article aims to trace the surrealism style in Indonesia through literature. The literature studies are done in two phases, aiming at different goals. In the first phase, we accessed literature collections about Surrealism through Modern Art frameworks and context. In the second phase, we used two online directories that index open access journals; DOAJ (Directory of Open Access Journals) and Garuda (Garba Rujukan Digital). The result is a list of analyses on how the Surrealism discussion appears through the Indonesian language journal articles. Through the list of findings, we also try to determine our upcoming research. We will try to expand surrealism discussion through moving image medium in Indonesia. Keywords: Surrealism, Indonesia, literature, painting, moving image